Pengaruh Jenis dan Dosis Fungi Mikoriza Arbuskula Pada Media Tanah Bekas Tambang Kapur Terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Mariche Dwi Denola; Armansyah; Auzar Syarif (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2026)
This study aimed to determine the interaction between the best AMF types and doses, the best AMF types, and the best doses on the growth of cocoa seedlings planted in after-lime mine soil. The experimental study was conducted from February to June 2025. This research was conducted at the Wire House, Faculty of Agriculture, Andalas University, Padang City, West Sumatra, in the Seed Science and Technology Laboratory, Faculty of Agriculture, Andalas University. Root colonization observations were conducted at the Plant Physiology Laboratory, Faculty of Agriculture, Andalas University, Padang. The study used a factorial completely randomized design (CRD) consisting of two factors. The first factor was the type of AMF, with three levels: Glomus sp., Gigaspora sp., and Acaulospora sp. The second factor was the AMF dosage, with four levels: 0 g/seedling, 10 g/seedling, 20 g/seedling, and 30 g/seedling. Data were analyzed statistically using the F-test at a 5% significance level. If the calculated F-test was greater than the table F-test, the analysis was continued with Duncan's New Multiple Range Test (DNMRT) at a 5% significance level. The results of this study indicate that there was no interaction between the type and dosage of AMF on the growth of cocoa seedlings planted in ex-lime mining soil. The Glomus sp. AMF was the best AMF for enhancing the growth of cocoa seedlings planted in ex-lime mining soil. Meanwhile, the AMF dosage of 30 g/seedling was the best for enhancing the growth of cocoa seedlings planted in ex-lime mining soil.